2020
DOI: 10.1186/s13052-020-0797-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pidotimod on recurrent respiratory infections in children with Down syndrome: a retrospective Italian study

Abstract: Background: Children with Down syndrome (DS) show a high susceptibility to recurrent infections (RI), caused by immune defects and abnormalities of the airways. Our goal was to investigate the effects of Pidotimod on RI prevention in children with DS, comparing immune and clinical parameters before (T0) and after (T1) the treatment with Pidotimod. Methods: The study was conducted at the Down syndrome outpatient Center of Bambino Gesù Children's Hospital, in Rome. We reviewed the medical records of all children… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Among the molecules capable of interfering in the innate and adaptive immune response, Pidotimod, an immunomodulatory agent able in increasing antigen presentation and promoting adaptive Th1-mediated immunity, showed good efficacy and safety when administered in, addition to a bacterial lysate, in children aged 3-12 years with PFAPA [11]. In their study, authors administered Pidotimod 200 mg/daily for 20 days for a minimum of 6 consecutive months and up to 36 months with a summer break of 4 to 6 months [10]; and reported that the healing rate of PFAPA symptoms was 68% (n = 25 patients), with 11% (n = 4 cases) in complete remission at the end of the second year of follow-up. Overall, 78% children (n = 29) experienced a marked decrease in the incidence of fever, a reduced antipyretic drugs and antibiotics use, a markedly improved quality of life as assessed by a decreased time lost from school for the children and work for the parents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the molecules capable of interfering in the innate and adaptive immune response, Pidotimod, an immunomodulatory agent able in increasing antigen presentation and promoting adaptive Th1-mediated immunity, showed good efficacy and safety when administered in, addition to a bacterial lysate, in children aged 3-12 years with PFAPA [11]. In their study, authors administered Pidotimod 200 mg/daily for 20 days for a minimum of 6 consecutive months and up to 36 months with a summer break of 4 to 6 months [10]; and reported that the healing rate of PFAPA symptoms was 68% (n = 25 patients), with 11% (n = 4 cases) in complete remission at the end of the second year of follow-up. Overall, 78% children (n = 29) experienced a marked decrease in the incidence of fever, a reduced antipyretic drugs and antibiotics use, a markedly improved quality of life as assessed by a decreased time lost from school for the children and work for the parents.…”
Section: Discussionmentioning
confidence: 99%
“…In light of evidence that an abnormal host immune response is featuring patients with PFAPA syndrome, immunostimulant drugs have been hypothesized to be new and potential molecules able to attenuate the inflammatory status in PFAPA syndrome, thus, preventing disease attacks. In this regard, Pidotimod, (PDT, 3-L-pyroglutamyl-L-thiaziolidine-4-carboxylic acid), a synthetic dipeptide molecule, showed significant immunomodulatory effects, especially in children suffering from respiratory tract infections [9,10]. By acting both on innate and adaptive immune response, Pidotimod administration has been significantly associated with a reduction of the number of infections, number of days of fever, a less severity of signs and symptoms, and, consequently, a reduction in use of antibiotics and symptomatic drugs [9].…”
Section: Introductionmentioning
confidence: 99%
“…As COVID‐19 presents as an acute severe respiratory syndrome and DS is by far the most frequent chromosomal disease with the highest susceptibility to develop respiratory infections and complications, 1 it seems timely to focus on this syndrome during the ongoing pandemic.…”
Section: Figurementioning
confidence: 99%
“…In light of evidence that an abnormal host immune response is featuring patients with PFAPA syndrome, immunostimulant drugs have been hypothesized to be new and potential molecules able to attenuate the in ammatory status in PFAPA syndrome, thus, preventing disease attacks. In this regard, Pidotimod, (PDT, 3-L-pyroglutamyl-Lthiaziolidine-4-carboxylic acid), a synthetic dipeptide molecule, showed signi cant immunomodulatory effects, especially in children suffering from respiratory tract infections [11,12]. By acting both on innate and adaptive immune response, Pidotimod administration has been signi cantly associated with a reduction of the number of infections, number of days of fever, a less severity of signs and symptoms, and, consequently, a reduction in use of antibiotics and symptomatic drugs [11, gure 1].…”
Section: Introductionmentioning
confidence: 99%